2013
DOI: 10.5607/en.2013.22.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Mimics the Effects of Endogenous Ovarian Hormones on Repeated Seizures Induced by Pentylenetetrazole in Rats

Abstract: In the present study, the effects of tamoxifen on pentylenetetrazole (PTZ)-induced repeated seizures and hippocampal neuronal damage in ovariectomized rats were investigated. Thirty seven virgin female Wistar rats were divided to: (1) control, (2) sham-PTZ, (3) sham-PTZ-tamoxifen (sham-PTZ-T), (4) Ovariectomized -PTZ (OVX-PTZ) and (5) OVX-PTZ-tamoxifen (OVX-PTZ-T) groups. The animals of groups 3 and 5 were injected by tamoxifen (10 mg/kg) on 7 consecutive days. After 7 days of tamoxifen injection, they also we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“… 38 , 39 , 40 It has been shown that seizures may lead to morphological changes such as production of dark neurons, in brain tissue. 10 , 32 Dark neurons, previously were considered as histological artifacts in neurosurgical biopsies 34 , 41 but later, they were seen after brain trauma. 34 , 42 Recently, it has been well documented that dark neurons are also produced without any trauma or mechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 , 40 It has been shown that seizures may lead to morphological changes such as production of dark neurons, in brain tissue. 10 , 32 Dark neurons, previously were considered as histological artifacts in neurosurgical biopsies 34 , 41 but later, they were seen after brain trauma. 34 , 42 Recently, it has been well documented that dark neurons are also produced without any trauma or mechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds have been shown to exert estrogen-like neuroprotective actions in the brain. Tamoxifen, one of SERMs, is extensively used in breast cancer 6 . In CNS, tamoxifen has both agonistic and antagonsistic effects on estrogen receptors 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen, one of SERMs, is extensively used in breast cancer 6 . In CNS, tamoxifen has both agonistic and antagonsistic effects on estrogen receptors 6 . There is also evidence that SERMs may affect mood, depression and anxiety 7 .…”
Section: Introductionmentioning
confidence: 99%
“…injected for 28 days. The doses of the treatments were based on previous studies reporting the antioxidant actions of the agents (Kumral et al, 2014;Reddy, 2009;Zheng et al, 2004;Wang et al, 2013;Gómez et al, 2009;Mansouri et al, 2013). Following the 28-day treatment period, epileptic seizure was induced by a single-dose of PTZ (45 mg kg −1 ), while the tap water-given control group was injected with saline.…”
Section: Methodsmentioning
confidence: 99%